The Winnipeg General Strike of 1919: An Illustrated History - Seager, Allen (Labour / Le Travail, 1995)
The article reviews the book, "The Winnipeg General Strike of 1919: An Illustrated History," by J. M. Bumsted.
Keywords: BOOKS -- Reviews; BUMSTED, J. M.; GENERAL strikes; Nonfiction; WINNIPEG General Strike of 1919: An Illustrated History (Book)